Phytochemical Evaluation and Antioxidant Activity of Holarrhena pubescens Wall. ex G.Don: Phytochemical Evaluation and Antioxidant Activity of Holarrhena pubescens Wall. ex G.Don - Arunprasath, A. (International Journal of Pharmaceutical & Biological Archive, 2018)
The selected medicinal plant Holarrhena pubescens Wall. ex G.Don belongs to the family Apocynaceae, and it was collected in hillock of Muthu Malai hill in Coimbatore, Tamil Nadu. In the present study, preliminary phytochemical screening of H. pubescens a medicinal plant was carried out. Qualitative phytochemical analysis of these plants confirms the presence of various secondary metabolites such as steroids, tannins, alkaloids, and phenols. The results suggest that the phytochemical properties for curing various ailments possess potential anti-inflammatory, antimicrobial, and antioxidant and leads to the isolation of new and novel compounds. Gas chromatography-mass spectrometry analysis showed the existence of various compounds with different chemical structures. The presence of various bioactive compounds confirms the application of H. pubescens for various ailments by traditional practitioners. However, isolation of individual phytochemical constituents may proceed to find a novel drug. Extracts from H. pubescens showed varying antioxidant (free radical scavenging) activities when compared to Vitamin C, and the results suggest that the antioxidant activity of H. pubecens may contribute to their claimed medicinal property.